Essential Shakespeare : - Bickley, Pamela (Bloomsbury, 2013)
"An introductory critical study for first year undergraduates which bridges the gap between A Level and university study. The book offers an accessible overview of key critical perspectives, early modern contexts, and methods of close reading, as well as screen and stage performances spanning several decades. Organised around the discussion of fourteen major plays, it introduces readers to the diverse theoretical approaches typical of today's English studies. This is a go-to resource that can be consulted thematically or by individual play or genre. Critical approaches can overwhelm students who are daunted by the quantity and complexity of current scholarship; Bickley and Stevens are experienced teachers at both A and university level and are thus uniquely qualified to show how a mix of critical ideas can be used to inform ways of thinking about a play" --